Step-by-step explanation:
Given : m∥n , ∠1= 50° , ∠2= 48° , and line s bisects ∠ABC
To prove = ∠3= 49°
Solution:
In figure, m∥n cut by traversal t.
So, ∠DEF = ∠ABC(alternative exterior angles)
∠1 + ∠2 = ∠4 + ∠5
∠ABC = ∠1 + ∠2 = 50° + 48° = 98°
Also given that s bisect angles ∠ABC.
∠4 = ∠5
∠ABC = ∠4 + ∠5 = 98°
∠4 + ∠4 = 98°
2∠4 = 98°
∠4 = 49°
∠4= ∠3 = 49° (vertically opposite angles)
∠3 = 49° ,hence proved
Answer:
C. Divide both sides of the inequality by 4 but don't flip the symbol.
Step-by-step explanation:
When you solve an inequality, you have to get the x by itself. So, in this inequality, the first thing you would do is divide both sides of the inequality by 4. The new and solved equation would look like this:
x ≥ -6
Because multiplying by a negative, dividing by a negative, or having negatives on both sides of the inequality was not involved in solving for x, flipping the symbol is not needed.
I really hope this helps! Have an amazing day :3
Answer: 64.6
Step-by-step explanation:
If you add up 63.7 and 65.4 and then divide by 2 you get 64.6.
The statement that is true about the equation 3(-y + 7) = 3(y + 5) + 6 is;
Statement A; The equation has one solution, y = 0
The given equation is;
3(-y + 7) = 3(y + 5) + 6
Expanding the brackets gives us;
-3y + 21 = 3y + 15 + 6
-3y + 21 = 3y + 21
Using subtraction property of equality, subtract 21 from both sides to give;
-3y = 3y
Using addition property of equality, add 3y to both sides to give;
-3y + 3y = 3y + 3y
6y = 0
Using division property of equality, divide both sides by 6 to get;
y = 0
Read more about factorization at; brainly.com/question/11000698
The missing statements are;
A. The equation has one solution, y = 0.
B. The equation has one solution, y = -1.
C. The equation has no solution.
D. The equation has infinitely many solutions.
Answer:
Infinite
Step-by-step explanation:
I hope this helps, if it doesn't then just message me and ill be more than happy to help :)